On the Ramanujan-Petersson conjecture for modular forms of half-integral weight - Gun, Sanoli; Kohnen, Winfried (Forum mathematicum, 2019)
We investigate the (still unknown) Ramanujan-Petersson conjecture about the growth of the Fourier coefficients of cusp forms of half-integral weight and prove that it is optimal, at least for newforms in the plus space.